2016
DOI: 10.3390/nu8100639
|View full text |Cite
|
Sign up to set email alerts
|

Time of Day and Training Status Both Impact the Efficacy of Caffeine for Short Duration Cycling Performance

Abstract: This project was designed to assess the effects of time of day and training status on the benefits of caffeine supplementation for cycling performance. Twenty male subjects (Age, 25 years; Peak oxygen consumption, 57 mL·kg−1·min−1) were divided into tertiles based on training levels, with top and bottom tertiles designated as ‘trained’ (n = 7) and ‘untrained’ (n = 7). Subjects completed two familiarization trials and four experimental trials consisting of a computer-simulated 3-km cycling time trial (TT). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
3
26
0
7
Order By: Relevance
“…At these sample sizes, the Type I error rate for the "possible" threshold is 22% to 45% and for the "likely" threshold is 12% to 22% (Fig 3A and 3B). Consistent with these calculations, we noticed numerous studies in which effects associated with large p-values (for H o =0)-often in the 0.2 to 0.3 range-were declared "likely" or higher by MBI [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. See Fig 4 for "Although parametric analysis was unable to demonstrate significant differences, magnitude-based inferences indicated that the change in 1-RM squat showed a likely benefit from PA on increasing lower body strength and a very likely benefit for increasing lean body mass (LBM)."…”
Section: Resultssupporting
confidence: 80%
“…At these sample sizes, the Type I error rate for the "possible" threshold is 22% to 45% and for the "likely" threshold is 12% to 22% (Fig 3A and 3B). Consistent with these calculations, we noticed numerous studies in which effects associated with large p-values (for H o =0)-often in the 0.2 to 0.3 range-were declared "likely" or higher by MBI [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. See Fig 4 for "Although parametric analysis was unable to demonstrate significant differences, magnitude-based inferences indicated that the change in 1-RM squat showed a likely benefit from PA on increasing lower body strength and a very likely benefit for increasing lean body mass (LBM)."…”
Section: Resultssupporting
confidence: 80%
“…We terminated our study search in April 2016 but the field of ergogenic supplements continues to evolve. Recently, studies has been published showing no effect on intense endurance performance from both bicarbonate (Callahan et al, 2016) and nitrate (Callahan et al, 2016) supplementation whereas caffeine has resulted in both unchanged (Cordingley et al, 2016) and improved performance (Boyett et al, 2016). A number of the included studies in the current meta-analysis also reported negative findings, so to what extent an actual publication bias toward positive results exits remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These include smoking [ 63 , 64 ], dietary vegetable intake [ 65 ], oral contraceptive use [ 66 , 67 ], pregnancy [ 68 ], menstrual cycle stage [ 69 ], training status [ 44 , 45 ], and hormone replacement therapy [ 70 ]. Other non-genetic, but controllable, factors affecting caffeine ergogenicity are related to the nature of caffeine ingestion, including caffeine dose [ 71 ], source [ 72 74 ], age [ 75 ], timing [ 76 ], time of day [ 76 , 77 ], and training status [ 78 , 79 ].…”
Section: Why Does This Individual Response Exist?mentioning
confidence: 99%